Use of manual electronic penetrometer in the evaluation of soil resistance in cropping systems with cover crops (Research, Society and Development, 2022)
Soil resistance to penetration directly interferes with the production of agricultural crops, harming the development of roots and consequently the absorption of water and nutrients, the no-tillage system has as one of its precepts the non-disturbing of the soil and with that the soil compaction. it is a consequence. The objective of this study was to evaluate different cover crops in consortium or mix, with and without soil conditioning, with the planting of corn in the resistance to soil penetration, at a depth of 0 to 35 cm. The experimental design was in randomized blocks with four replications and eight treatments implanted before soybean cultivation, T1- single corn with conventional fertilization; T2 – single corn with only organic fertilization; T3- corn with organomineral fertilization; T4- corn with biochar; T5- mix of cover crops (crotalaria spectabilis+forage turnip+brachiaria ruziziensi); T6- corn intercropped with Brachiaria ruziziensis; T7- corn intercropped with sunn hemp; T8- mix of cover crops + biochar. There was a significant difference at 5% probability only at two depths, from 0 to 5 cm where treatments 7 and 8 were the ones with the lowest penetration resistance and at the depth of 30 to 35 cm where treatment 1 was the one with the lowest resistance the penetration.